2008
DOI: 10.1111/j.1439-0388.2008.00722.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation at the alpha‐1‐fucosyltransferase (FUT1) gene in Asian wild boar and Chinese and Western commercial pig breeds

Abstract: Escherichia coli F18 bacteria producing enterotoxins and/or shigatoxin (ETEC/STEC) are main pathogens that cause oedema disease and postweaning diarrhoea in piglets, and alpha-1-fucosyltransferase (FUT1) gene has been identified as a candidate gene for controlling the expression of ETEC F18 receptor. The genetic variations at nucleotide position 307 in open reading frame of FUT1 gene in one wild boar breed and 20 western commercial and Chinese native pig breeds were investigated by polymerase chain reaction-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
36
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 4 publications
1
36
0
Order By: Relevance
“…It is clear that FUT1 and FUT2 loci are associated with E. coli F18 adhesion resistant animals in these breeds. The research confirmed that a variation in the alpha 1 fucosyltransferase (FUT1) gene is the causative mutation for adhesion-resistant animals (Michaels et al, 1994;Bao et al, 2008). In addition to the F18-resistance marker, a marker for E. coli K88 has been identified (Michaels et al, 1994).…”
Section: Introductionmentioning
confidence: 57%
“…It is clear that FUT1 and FUT2 loci are associated with E. coli F18 adhesion resistant animals in these breeds. The research confirmed that a variation in the alpha 1 fucosyltransferase (FUT1) gene is the causative mutation for adhesion-resistant animals (Michaels et al, 1994;Bao et al, 2008). In addition to the F18-resistance marker, a marker for E. coli K88 has been identified (Michaels et al, 1994).…”
Section: Introductionmentioning
confidence: 57%
“…Meijerink et al (1997;2000) reported that a mutation in the M307 locus of FUT1 confers resistance to E. coli infections. However, the distributions of genotypes at this locus are highly skewed among Chinese porcine breeds; therefore, this gene is not suitable for breeding disease resistance (Bao et al, 2008). So screening and identifying the gene conferring resistance to E. coli F18 and search for novel genetic markers are very important.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this research, we and other Chinese researchers have systematically analyzed the FUT1-coding region in nearly 30 Chinese native pig breeds and foreign pig breeds. The variation of FUT1 gene on M307 locus, which has been used as a genetic marker in foreign breeds, displays an extremely skewed distribution in native Chinese pig breeds compared to foreign breeds (Bao et al 2008;Yan et al 2003), and the presence or absence of the M307 locus does not significantly influence the expression level of FUT1 (Bao et al 2012a, b). This makes the development of resistance to ETEC F18 in local Chinese pig breeds difficult and problematic.…”
Section: Introductionmentioning
confidence: 99%